Hubungan Budaya Akademik dan Budaya Organisasi dengan Kinerja Guru - Arif, Miftakhul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2019)
This study aims to identify and test the empirical data on the relationship of academic culture and organizational culture with teacher performance separately or simultaneously. In this study, the authors used survey method with the correlational approach regresional the quantitative data obtained from the object of research is school teachers Islam Al-Azhar BSD. Samples were as many as 93 respondents Islamic School teacher population of Al-Azhar BSD in the academic year 2016-2017. The data collection was done by using a questionnaire/questionnaire, observation, and documentation. Type of analysis is correlation and regression analysis were described descriptively. The results of this study are: First, There is a positive and significant academic culture on teacher performance with the correlation coefficient (r) of 0,804 and a coefficient of determination (R2) of 64,6%. Secondly, There is a positive and significant relationship of organizational culture on teacher performance with the correlation coefficient (r) of 0,736 and a coefficient of determination (R2) of 53,7%. Thirdly, there is a positive and significant academic culture and organizational culture simultaneously on teacher performance. The correlation coefficient of 0.813 while the coefficient of determination of 66,1%.